Rational use of antimicrobials in dentistry during pregnancy - Lodi, Karina Bortolin; das Chagas e Silva de Carvalho, Luis Felipe; Koga-Ito, Cristiane Yumi [UNESP]; Pinheiro Carvalho, Valeria Abrantes; da Rocha, Rosilene Fernandes [UNESP] (Medicina Oral S L, 2009)
The use of medicines during pregnancy deserves special attention from dentists due to the potential risks to fetal development. The prescription of antimicrobial drugs during this period must be based not only on the etiology of the disease but also on the drug's effect on the embryo, which may be toxic, possibly leading to irreversible lesions. Interest in studies of the teratogenic effects of drugs increased in response to reports of the high incidence of phocomelia in patients treated with thalidomide. Although teratogenicity has long been known, pregnant women today are still exposed to this risk. The effects of drugs depend on the level of susceptibility of the fetus and on the period of exposure during pregnancy. In this context, and considering the paucity of studies on this subject in dentistry, the aim of this review was to offer an up-to-date compilation of data on the antimicrobial drugs most frequently used during pregnancy and the effects of their use.
Keywords: Pregnancy; antimicrobials; odontology